Political socialization in flux? Linking family non-intactness during childhood to adult civic engagement - Timo Hener; Helmut Rainer; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Over the last several decades, there has been a widespread decrease in civic engagement coinciding with a breakdown in traditional family structures in many countries throughout the developed world. According to Putnam in Bowling alone (2000), however, none of the major declines in civic engagement can be accounted for by the decline in traditional family structures. In this paper, we seek to contribute a robust picture of how adult civic engagement is affected by growing up in a non-intact family. Using 26 waves of annual longitudinal data from the German Socio-Economic Panel, we construct various measures of family structure during childhood, and perform both cross-sectional and sibling difference analyses for different indicators of young adults' civic engagement. Both exercises reveal a significant negative relationship between growing up in a non-intact family and children's civic, social and political engagement as adults. We argue that this finding is consistent with causation rather than selection as the explanation for the negative relationship, and provide several robustness checks to support this claim.
Keywords: J12; 330; childhood family structure; civic engagement; social capital